Measuring secondhand smoke in homes in Malaysia: A feasibility study comparing indoor fine particulate (PM 2.5 ) concentrations following an educational feedback intervention to create smoke-free homes during the COVID-19 pandemic - Aziemah Zulkifli+; Nurul Latiffah Abd Rani+; Raisya Nur Syazmeen Abdul Mutalib; Ruaraidh Dobson; Tengku Azmina Engku Ibrahim; Norul Hernani Abd Latif; Rachel O’Donnell; Isabelle Uny; Emilia Zainal Abidin; Sean Semple (Tobacco Induced Diseases, 2022)
Introduction Extensive regulations have been introduced to reduce secondhand smoke (SHS) exposure among non-smokers in Malaysia. However, there is still a need to encourage behavior change of smokers in relation to making homes smokefree. This feasibility study aimed to use low-cost air pollution monitors to quantify SHS concentrations in Malaysian households and to explore the practicality of using personalized feedback in educating families to make their homes smoke-free.